Neoadjuvant chemoradiotherapy combined with sequential perioperative toripalimab in locally advanced esophageal squamous cell cancer - Qiang Liu; Qing Ye; Xin Xu; Lei Shen; Yao Zhang; Bin Hu; Haiyan Chen; Xiaojing Zhao; Zhiyong Sun; Haiping Lin; Ling Rong; Xiaohang Wang; et al. (Journal for ImmunoTherapy of Cancer)
Background Programmed death 1 (PD-1) inhibitor demonstrated durable antitumor activity in advanced esophageal squamous cell carcinoma (ESCC), but the clinical benefit of perioperative immunotherapy in ESCC remains unclear. This study evaluated the efficacy and safety of neoadjuvant chemoradiotherapy (nCRT) combined with the PD-1 inhibitor toripalimab in patients with resectable ESCC.Methods From July 2020 to July 2022, 21 patients with histopathologically confirmed thoracic ESCC and clinical staged as cT1-4aN1-2M0/cT3-4aN0M0 were enrolled. Eligible patients received radiotherapy (23 fractions of 1.8 Gy, 5 fractions a week) with concurrent chemotherapy of paclitaxel/cisplatin (paclitaxel 45 mg/m2 and cisplatin 25 mg/m2) on days 1, 8, 15, 22, 29 and two cycles of toripalimab 240 mg every 3 weeks after nCRT for neoadjuvant therapy before surgery, four cycles of toripalimab 240 mg every 3 weeks for adjuvant therapy after surgery. The primary endpoint was the major pathological response (MPR) rate. The secondary endpoints were safety and survival outcomes.Results A total of 21 patients were included, of whom 20 patients underwent surgery, 1 patient refused surgery and another patient was confirmed adenocarcinoma after surgery. The MPR and pathological complete response (pCR) rates were 78.9% (15/19) and 47.4% (9/19) for surgery ESCC patients. 21 patients (100.0%) had any-grade treatment-related adverse events, with the most common being lymphopenia (100.0%), leukopenia (85.7%), neutropenia (52.4%). 14 patients (66.7%) had adverse events of grade 3 with the most common being lymphopenia (66.7%). The maximum standardized uptake value and total lesion glycolysis of positron emission tomography/CT after neoadjuvant therapy well predicted the pathological response. The peripheral CD4+%, CD3+HLA-DR+/CD3+%, CD8+HLA-DR+/CD8+%, and IL-6 were significant differences between pCR and non-pCR groups at different times during neoadjuvant therapy. Three patients had tumor relapse and patients with MPR have longer disease-free survival than non-MPR patients.Conclusions nCRT combined with perioperative toripalimab is effective and safe for locally advanced resectable ESCC. Long-term survival outcomes remain to be determined.Trial registration number NCT04437212.